How consumers' perceptions differ towards the design features of mobile live streaming shopping platform: A mixed-method investigation of respondents from Taobao Live. (November 2022) - Xiao, Quan; Wan, Shanshan; Zhang, Xing; Siponen, Mikko; Qu, Lu; Li, Xia
Abstract: Mobile Live Streaming Shopping (MLSS) has become the most rapidly growing e-commerce business. However, there is a dearth of theoretical concern on the MLSS platform designing issue - the key factor affecting business success. Based on the axiomatic design theory, a systematic view of design features of MLSS platform is given, and a three-layer model including thirteen design features is built. The perceived differences of consumers across design features and individual characteristics, as well as the prioritization strategies of MLSS platform are derived with a mixed-method schema. The study provides fine-grained insights for enhancing the differentiated consumer experience by optimizing and improving the design of MLSS platforms.